(3LQGFe GdJMQjV YHQ THcGJ GdJhGUd GdGLJeGYj hYdGbJgG HGJLGgGJ GdTHGH fMh bVGjG GdTCf GdYGe (B/s - (3,ejQfG YQaI CMeO YQaIs; (3TQja OQhjT GddHGfs (2024)
(3JSYi GdOQGSI Gdi JMbjb gOa QFjS jJeKd aj (B: (3QUO hJMdjd hJaSjQ LQGFe GdJMQjV Ydi THcGJ GdJhGUd GdGLJeGYj(B((3ajS Hhc(B) (3, hCgOGa aQYjI(B: (3hJMdjd GdeVehf GdebOe ddLQGFe GdJMQjVjI GdefThQI YHQ UaMGJ UaMGJ GdUMa hUaMGJ GdfTWGA Ydi THcGJ GdJhGUd GdGLJeGYj (B((3ajS Hhc(B)(3, QUO BdjGJ GdJMjR hGdJhGRf ddeVehf GdebOe Ydi THcGJ GdJhGUd GdGLJeGYj (B((3ajS Hhc(B) (3ShGA aj UaMGJ GdeDSSGJ hGdGTNGU GdeDjOI Gh UaMGJ GdeDSSGJ h GdGTNGU PGJ GdGJLGI GdeYGQV, hQUO GdVhGHW GdegfjI GdMGceI dBdjGJ GdeeGQSI GdUMajI Ydi THcGJ GdJhGUd GdGLJeGYj ajeG jJYdb HLQGFe GdJMQjV NGUI aj UaMGJ GdUMa GdeUQjI Ydi THcGJ GdJhGUd GdGLJeGYj (B((3ajS Hhc(B) (3ShGA GdUaMGJ GdeDjOI ddfXGe Gh GdUaMGJ PGJ GdGJLGI GdeYGQV, hGdJYQa Ydi YdGbI feW edcjI GdUMa dUaMGJ THcGJ GdJhGUd GdGLJeGYj HGdeVehf GdebOe hhLhO LQjeI GdJMQV, hGdJejjR Hjf GdJMQjV h NWGH GdcQGgjI Ydi ehGbY GdJhGUd GdGLJeGYj(B((3ajSHhc(B).s
The study seeks to achieve a main goal, which is: monitoring, analyzing, and interpreting incitement crimes on social networks (Facebook), and sub-objectives: analyzing the content presented for incitement crimes published across the pages of newspaper pages and the pages of activists on social networks (Facebook), monitoring bias mechanisms. There is balance in the content presented on social media networks (Facebook), whether on the pages of institutions and individuals who support it or the pages of institutions and persons with an opposing trend. Monitoring the professional controls governing the mechanisms of journalistic practice on social media networks with regard to crimes of incitement, especially on the pages of Egyptian newspapers on social media networks (Facebook), whether pro-regime pages or pages with an opposition orientation, and identifying the relationship between the pattern of newspaper ownership of social media pages and the content provided. The existence of the crime of incitement, and the distinction between incitement and hate speech on social networking sites (Facebook).
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B323-344.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdUMGaIs; (3YHQ THcGJ GdJhGUd GdGLJeGYj s -- (3HEJLGgGJ GdTHGH s -- (3LQGFe GdJMQjV s